2009
DOI: 10.1590/s1677-04202009000100002
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of Eichhornia crassipes [Mart.] Solms to the combined exposure to excess nutrients and Hg

Abstract: . The accumulation of P and S was reduced by the addition of HgCl 2 , and also the P and K concentrations in emerged and submerged parts respectively decreased. In contrast, the addition of HgCl 2 increased Ca and Mg concentrations in submerged parts. Furthermore, the concentration ratios of submerged/ emerged parts for Ca, Mg and P were also reduced by the addition of HgCl 2 . The interaction of HgCl 2 and KNO 3 was synergistic and decreased F v /F m , total chlorophyll content and P and Mn concentrations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…(Solms)). Several studies point out that this plant species is tolerant to inhospitable pollution conditions (Caldelas et al 2009) and are able to accumulate nutrients and heavy metals, including mercury (Cordes et al 2000;Jayaweera & Kasturiarachchi 2004;Gardea-Torresdey et al 2005). Thus, this could justify our finding besides corroborating the one suggested by Jayaweera & Kasturiarachchi (2004), that this plant is promising in the bioremediation of mercury present in eutrophic waters.…”
Section: Mercury Concentration In River Water Samples By Uv-vissupporting
confidence: 83%
“…(Solms)). Several studies point out that this plant species is tolerant to inhospitable pollution conditions (Caldelas et al 2009) and are able to accumulate nutrients and heavy metals, including mercury (Cordes et al 2000;Jayaweera & Kasturiarachchi 2004;Gardea-Torresdey et al 2005). Thus, this could justify our finding besides corroborating the one suggested by Jayaweera & Kasturiarachchi (2004), that this plant is promising in the bioremediation of mercury present in eutrophic waters.…”
Section: Mercury Concentration In River Water Samples By Uv-vissupporting
confidence: 83%
“…According to Greco and de Freitas [30], this macrophyte grows best at high temperatures, as experienced in Brazil. E. crassipes has previously been tested for the phytoremediation of urban wastewater [31], cyanide [32], and mercury [33] and has been assessed as useful and appropriate for such purposes. However, using E. crassipes in a Green Liver System can also have adverse effects, as this plant might reduce the oxygen level in the surface region of the water column and consequently provide the ideal environment for the development of mosquitos and snails, acting as vectors for diseases [34].…”
Section: Second Trial and Final Layoutmentioning
confidence: 99%
“…The species E. crassipes, known as "aguapé" or "water hyacinth," is a floating aquatic macrophyte, native to South America and belongs to the family Pontederiaceae [31], highly tolerant to polluted environments and effective for extracting nutrients and metals such as Cd, Pb and Hg. Research has shown that for elements such as Hg, it has great absorption properties, with only the characteristic of chlorosis in the plant when exposed, without drastically affecting its growth over a long period with a certain quantity of mercury, counting on this attribute even in the remediation of water with high levels of K and NO 3− [33]. Also, it was demonstrated the ability of this species to absorb many other elements such as Cd, Cu, Ni, Pb, Zn, with copper being the most absorbed in the root region, presenting a high value bioconcentration factor; for lead, when presented at low concentrations demonstrates large accumulation at roots, not finding values as high for the other metals in this study [34].…”
Section: Eichhornia Crassipesmentioning
confidence: 99%